2014
DOI: 10.1177/0093854814553222
|View full text |Cite
|
Sign up to set email alerts
|

Using Dynamic Factors to Predict Recidivism Among Women

Abstract: Using a sample of 497 Canadian women released into the community from federal prisons, this study examined the extent to which seven dynamic risk factors prospectively assessed at 6-month intervals (four waves) change over time and predict recidivism. Results obtained from a series of within-subject ANOVAs indicate that with the exception of substance abuse, all dynamic risk factors (i.e., employment, marital/family, community functioning, personal/emotional, criminal associates, and criminal attitudes) decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 61 publications
5
39
0
Order By: Relevance
“…All four types of risk factors are relevant to risk assessment (Roles 1 and 2 above). Variable markers and variable risk factors are relevant to monitoring changes in risk over time (for demonstrations, see Cohen & VanBenschoten 2014, Greiner et al 2015, Howard & Dixon 2013, Jones et al 2010. But only causal risk factors are directly relevant to risk reduction (Role 3 above).…”
Section: Risk Promotive and Proxy Factorsmentioning
confidence: 99%
“…All four types of risk factors are relevant to risk assessment (Roles 1 and 2 above). Variable markers and variable risk factors are relevant to monitoring changes in risk over time (for demonstrations, see Cohen & VanBenschoten 2014, Greiner et al 2015, Howard & Dixon 2013, Jones et al 2010. But only causal risk factors are directly relevant to risk reduction (Role 3 above).…”
Section: Risk Promotive and Proxy Factorsmentioning
confidence: 99%
“…It has also been suggested that Theory and Application of Dynamic Risk -21 including at least three waves of assessment increases the probability of detecting change (Brown, Amand, & Zamble, 2009). A recent multi-wave study by Greiner, Law, and Brown (2014) illustrated the tracking of seven major theorised dynamic risk factors (employment, personal/emotional factors, substance use, criminal attitudes, criminal associates, family functioning, and community functioning) among female offenders following their release from prison, across four assessment waves at six-monthly intervals. They found that all seven factors were significantly related to survival time without reoffending in the community, and that prediction was improved by their use of multiple assessments of dynamic risk across time.…”
Section: Theory and Application Of Dynamic Risk -18mentioning
confidence: 99%
“…Even more uniquely, few prospective multi--wave re--entry studies have attempted to test whether re--assessment timing is related to more accurate prediction. Rather, these studies have examined (a) change processes and their relation to recidivism (e.g., Babchishin, 2013;Blanchard, 2013;Labrecque et al, 2014;Michel et al, 2013), (b) the general relationship between dynamic factors and recidivism (e.g., Greiner, Law, & Brown, 2014), and (c) whether repeated assessments are incrementally related to recidivism beyond static risk scales (e.g., Brown, St. Amand, & Zamble, 2009;Morgan et al, 2013). Although these research questions (change, predictive validity, and incremental prediction) represent important goals, examining assessment proximity requires testing whether a dynamic measure can add incremental prediction beyond its own prior measurement.…”
Section: Retrospective Matched Designsmentioning
confidence: 99%